Thermal decomposition behavior of tobacco stem Part I: TGA-FTIR-MS analysis - POLAT, SEVGİ (TAYLOR & FRANCIS INC, 2016)
In the present study, the thermal degradation behavior of tobacco stem was examined by means of a thermogravimetric analyzer (TGA) under nitrogen atmosphere at temperature range of 25-1,000 degrees C. The TG curve indicated that the pyrolysis process of tobacco included three zones, and main pyrolysis occurred in the second zone by means of the decomposition of hemicellulose, cellulose, and lignin in a temperature range of 180-540 degrees C. Furthermore, the gases evolved during the degradation were analyzed simultaneously via TGA coupled with a Fourier transform infrared spectrometer (FTIR) and mass spectrometer (MS). Carbon dioxide, methane, water, formaldehyde, and propanal were the main volatiles detected via MS and confirmed by FTIR.
Keywords: Biomass; pyrolysis; TGA-FTIR-MS; thermogravimetry; tobacco stem; PYROLYSIS; KINETICS; WASTE